Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, December 21, 1929 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1929)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, December 21, 1929. June 14th found Hawley at St. Augustine and he had time to write to Warner a voluminous letter, telling how he dealt with a crooked war profiteer, describing a romantic episode of revenge and expressing his delight with the success of the Press under Warner’s editorship.
1 electronic record. Scanned newspaper article. 1 image scans. 22.7 MB (23,851,843 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 22.7 MB (23,851,843 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers